2021
DOI: 10.3389/fmicb.2021.672333
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interaction Networks Among Cyanolichens of a Tropical Biodiversity Hotspot

Abstract: Interactions within lichen communities include, in addition to close mutualistic associations between the main partners of specific lichen symbioses, also more elusive relationships between members of a wider symbiotic community. Here, we analyze association patterns of cyanolichen symbionts in the tropical montane forests of Taita Hills, southern Kenya, which is part of the Eastern Afromontane biodiversity hotspot. The cyanolichen specimens analyzed represent 74 mycobiont taxa within the order Peltigerales (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 78 publications
2
23
2
Order By: Relevance
“…Among the mycobionts, 58% lineages shared its photobiont with at least one other mycobiont, showing the presence of both generalist and specialist lineages. The taxa with apothecia were more generalist with their photobiont than the species lacking apothecia or with vegetative structures reproduction (Kaasalainen et al, 2021), which corroborate with the hypothesis that symbiotic dispersing lichens may facilitates the re-establishment of sexually dispersing species (Belinchón et al, 2015;Kaasalainen et al, 2021;Svensson et al, 2016).…”
Section: Interactions Between Cyanolichens Mycobiont and Photobiont I...supporting
confidence: 83%
“…Among the mycobionts, 58% lineages shared its photobiont with at least one other mycobiont, showing the presence of both generalist and specialist lineages. The taxa with apothecia were more generalist with their photobiont than the species lacking apothecia or with vegetative structures reproduction (Kaasalainen et al, 2021), which corroborate with the hypothesis that symbiotic dispersing lichens may facilitates the re-establishment of sexually dispersing species (Belinchón et al, 2015;Kaasalainen et al, 2021;Svensson et al, 2016).…”
Section: Interactions Between Cyanolichens Mycobiont and Photobiont I...supporting
confidence: 83%
“… Kaasalainen et al (2021) demonstrated that cyanolichens share photobionts and revealed the presence of photobiont-mediated lichen guilds. Most of the mycobionts shared photobionts with other non-related fungal species but other photobiont-mycobiont pairs remained isolated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sporeproducing lichens that require a compatible photobiont upon reproduction are indirectly facilitated by the asexual lichens within their guild already established in that environment 28 . Previously, guilds have been defined by photobiont taxonomic identity, but this characterisation has been constrained by the scope of the data sets, which have often included a limited amount of species or geographical locations 16,21,[30][31][32][33][34] . An aggregated network perspective allows us to tackle the structural signature of lichen guilds and provides a solid foundation to address how the general patterns of association in the lichen symbiont network affect its robustness.…”
Section: Discussionmentioning
confidence: 99%
“…Guild organization has been traditionally linked to photobiont identity (or "photobiont-mediated guild"), and more precisely, at the genus level 27,31,47 . Following this approach, Figure 4a shows the PMAN where species have been labelled according to the genus of their closest photobiont (using a label propagation algorithm, see Methods).…”
Section: Differences Between Topological Versus Taxonomic Signatures ...mentioning
confidence: 99%
See 1 more Smart Citation